P221 Home parenteral nutritional support in paediatric chronic intestinal failure – a single asian centre experience. (6th June 2017) - Buang, Siti Nur Hanim; Logarajah, Veena; Lan, Neo Swee; Liwanag, Maria Janelle; Bixia, Ang; Ong, Christina
Abstract : Background: Parenteral nutrition (PN) is the mainstay of treatment in children with chronic intestinal failure. We review our experience in home parenteral nutrition and describe outcomes of long term home PN therapy. Methods: A retrospective cohort study was conducted by retrieving clinical records of patients with primary digestive diseases who were on home parenteral nutrition between July 2014 to July 2016. Results: 13 patients (4 boys, 9 girls) received PN for more than 2 months. Out of these, 8 patients required PN therapy for more than 6 months. Main indications for long-term PN included chronic intestinal pseudo-obstruction syndrome (CIPOS, 38%), short bowel syndrome (SBS, 54%) and inflammatory bowel disease (IBD, 8%). Median age for initiation of PN was 1.7 years. Median duration of PN therapy was 1.4 years. 6 patients (46%), all with SBS, were successfully weaned off PN. One of the major complications of long term PN was central line-associated bloodstream infection (CLABSI). Incidence of CLABSI was 5.3 per 1000 catheter days. After implementation of use of Taurolidine-citrate solution (TCS), a catheter-lock solution, incidence of CLABSI improved with a pre and post-TCS CLABSI rate ratio of 0.17 (95% CI 0.04–0.52, p<0.001). There was no biochemical evidence of intestinal failure associated liver disease (IFALD) in all patients. This may be, in part, related to our practice of using SMOF lipid for patients requiring more than 2 weeks of PN. Only 2 patients exhibited lower final BMI Z-scores of < −2. There was a 100% survival in this study group. Conclusions: PN is a safe and crucial modality of treatment in children with chronic intestinal failure. SBS forms the largest subgroup in our paediatric intestinal failure population. However, patients in this subgroup were also more likely to be weaned off PN. Incidence of CLABSI can be effectively controlled with introduction of TCS. Incidence of IFALD can also be reduced with SMOF and other new lipids.